"An Index of Gentility": Representations of Needlework in Dombey and Son. (2nd January 2023) - Chen, Houliang
Abstract: Enlightened by scholarships in recent decades about the cultural significance of women's embroidery, this article attends to the scenes and activities featuring needlework in Charles Dickens's Dombey and Son . Through his representations of the nineteenth-century needlework language in this novel, Dickens provides for readers a window into Victorian women's everyday performance of embroidery. By focusing on his representations of needlework in the novel, this article reveals how the seemingly trivial performance of embroidery were embedded in Victorian schemas of gender and class configuration, and more importantly, how Dickens has artistically represented—while wishfully reproduced—the Victorian ideal of the gender divide through his rendering of needlework language.